(untitled) (Global Journal of Medical Research, 2023)
Epileptic grid electricity and frequent power blackouts in the night at LMIC neonatal centres hide behind frontline morbidities but contribute significantly to poor treatment outcomes at these centres Power blackouts make it hard for clinicians and nurses to see clearly when attending to patients in the dark Hence many patients have lost their lives during the mistakeprone poor visual setting This situation gets worse for centres located at more remote regions of LMICs where power outages could last for many days A recently published article on neonatalrescue- scheme concept proposed the reversal in neonatal traffic by taking the interventions to rural places where more needy neonates are to save them Therefore it becomes imperative to develop a reliable solar system of independent and sustainable technology that can guarantee dusk-to-dawn facility lighting at such remote locations which may not have grid electricity